Changes in the nitrate assimilation pathway serve as a component of maize stress response to competition cues - Kramer, William; Amirsadeghi, Sasan; McKenzie-Gopsill, Andrew; Swanton, Clarence J. (Frontiers in Plant Science, 2025)
The impact of plant competition cues on nitrate levels and their assimilation in major crop plants remains largely unknown. This study investigated how low red to far-red (R:FR) light, a signal of plant competition, affects nitrate levels and assimilation in maize and soybean seedlings. Maize and soybean seedlings were exposed to low R:FR light conditions (R:FR ≈ 0.5) that mimicked nearby weeds or artificial sources. Additional treatments included individual soybean seedlings subjected to a soybean canopy. Biochemical assays and RNA-sequencing were used to assess nitrate levels, assimilation-related enzymes, and gene expression. Low R:FR light led to increased leaf nitrate levels in maize by 95% and 52% compared to the weed-free control (R:FR ≈ 2.8), and in soybean by 50% and 63%, while ammonium levels remained unchanged. A 37% increase in leaf nitrate level was also observed in soybean exposed to canopy conditions. In maize, nitrate accumulation was linked to reduced activity of ferredoxin-dependent glutamine:2-oxoglutarate aminotransferase (fd-GOGAT), while activities of nitrate reductase, nitrite reductase, glutamine synthetase, and NADH-GOGAT were unaffected. RNA-sequencing of maize leaves did not show altered expression of tonoplast localized nitrate transporter genes. These findings suggest that low R:FR light, as a plant competition cue, promotes nitrate accumulation in maize and soybean, potentially by altering nitrate assimilation pathways rather than transport or storage. This response may influence crop growth and metabolism under competition stress.